Relation with Knowledge in the Full-Time School - Maria Celeste Reis Fernandes Souza; Bernard Charlot (Universidade Federal do Rio Grande do Sul, 2016)
This article presents partial results of a research that seeks to understand the relationships that students of final years of elementary school establish with knowledge and the Full-Time School. The theoretical and methodological frameworks are the studies of Bernard Charlot on the relation to knowledge. The analysis highlights the binomial protection/education, and the relationship expansion of time and learning with its tensions and contradictions. The conclusions indicate that the full-time can not be a simple extension of the current school, but should be a space-time where learning makes sense, offer new cultural opportunities and not hinder institutional or individual projects that have real value of formation.